2015
DOI: 10.2355/isijinternational.isijint-2015-272
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Stand-alone Powered Exoskeleton Robot Suit in Steel Manufacturing

Abstract: Handling heavy-load materials is the most common operation in iron and steel making processes. There are numerous operations in which workers directly deal with heavy loads without equipment. The refractory constructions in the converter and AOD (Argon Oxygen Decarburization) furnaces are representative examples. Transferring thousands of heavy materials repeatedly over a long period of time can not only cause musculoskeletal diseases, which occur 70% on the waist and 30% on other parts such as wrists, elbows,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…If exoskeletons achieved reductions in the mechanical stressors associated with MMH tasks, they would have the potential to reduce high rates of WMSDs seen in many industries. A number of studies have been published about the use of exoskeletons in reducing MSDs in steel manufacturing, construction, and automobile manufacturing and healthcare …”
Section: Potential Benefitsmentioning
confidence: 99%
“…If exoskeletons achieved reductions in the mechanical stressors associated with MMH tasks, they would have the potential to reduce high rates of WMSDs seen in many industries. A number of studies have been published about the use of exoskeletons in reducing MSDs in steel manufacturing, construction, and automobile manufacturing and healthcare …”
Section: Potential Benefitsmentioning
confidence: 99%
“…Active exoskeletons seem to be more promising in assisting workers and reducing the risk of lumbar vertebral injuries due to the higher versatility of the control system and external power source. Over the last decade, several active exoskeletons have been developed for lifting assistance worldwide (Naruse et al, 2005 ; Kobayashi and Nozaki, 2007 ; Tanaka et al, 2008 ; Aida et al, 2009 ; Kadota et al, 2009 ; Kobayashi et al, 2009 ; Muramatsu et al, 2011 ; Li, 2013 ; Yu et al, 2015 ) and were demonstrated to reduce the musculature effort of the back extensor muscles (Li, 2013 ; Muramatsu et al, 2013 ). However, in many cases the control systems do not independently detect the user's intention, and therefore are unable to automatically trigger the delivery of the assistance at the right moment: power assistance is usually manually triggered by users with extra joysticks or control buttons.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that today exoskeletons are introduced in different occupational fields—such as the industrial sector [ 3 , 5 ], construction [ 19 , 20 , 21 ], automotive industry [ 22 ], logistics [ 23 ], and steel manufacturing [ 24 ]—with the promise of improving the quality of work by combining human intelligence with exoskeleton assistance, their use in workplaces still needs to be investigated carefully. Considerations on the suitability of exoskeletons, their costs, and their impacts on the occupational safety and health of workers are required [ 25 ].…”
Section: Introductionmentioning
confidence: 99%